Immobilization of Candida antractica lipase type B by adsorption on activated carbon - Rodrigues, D. S. (Array, 2008)
The immobilization of Candida antarctica lipase type B on activated carbon was studied. Adsorption conditions were investigated in order to improve enzyme activity and stability in organic media. Results showed that biocatalyst activity and recovered activity were improved with increasing concentrations of ammonium sulphate on the supernatant during enzyme adsorption. Hydrophobic interactions were the driving force of the immobilization process. Nevertheless, the specific and recovered activity of the immobilized enzyme is affected by pH of adsorption, and best results were obtained when lipase adsorption was conducted near the enzyme isoeletric point (pI 6.0). Operational stability of the immobilized enzyme was markedly improved when lipase loading was increased from 74.15 U g–1 to 112.34 U g–1. After the sixth cycle of butyl butyrate synthesis, it retained around 10 % of the initial activity. Derivatives prepared in this work were tested and compared to a commercial derivative and results showed that they were a suitable biocatalyst to be used in the synthesis of flavours, such as butyl butyrate